1996
DOI: 10.1007/bf02305763
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal carcinoma and brain metastasis: Distribution, treatment, and survival

Abstract: Surgical removal of colorectal metastatic brain lesions results in significantly increased survival time, regardless of the status of the noncerebral systemic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
117
2
8

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 31 publications
6
117
2
8
Order By: Relevance
“…Studies of WBRT alone in patients with CRC have demonstrated poor outcomes, with survival ranging from 2.2 months to 4 months. 5,10,17,27,28 In the current study, all patients with >3 metastases and all patients in RPA Class III received WBRT as their primary treatment. Despite these adverse characteristics, patients who received upfront WBRT demonstrated a median survival (5.3 months) that was similar to that of patients who underwent surgery or SRS as their primary treatment.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies of WBRT alone in patients with CRC have demonstrated poor outcomes, with survival ranging from 2.2 months to 4 months. 5,10,17,27,28 In the current study, all patients with >3 metastases and all patients in RPA Class III received WBRT as their primary treatment. Despite these adverse characteristics, patients who received upfront WBRT demonstrated a median survival (5.3 months) that was similar to that of patients who underwent surgery or SRS as their primary treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, numerous reports have indicated that selection for surgical resection is a positive prognostic factor, 5,10,19,27 although the improvements in survival likely relate to a low tumor burden and the general health of the patients who are selected for surgical resection. For example, Farnell et al 17 reported that 45 patients who had a solitary BM from CRC who underwent surgical resection had a median survival of 45 weeks compared with 17 weeks for patients who had a single lesion and received WBRT alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous autopsy studies have shown that the incidence of brain metastases from colon cancer is less than 4% [1][2][3][4]. The most common primary sites are the sigmoid colon and rectum [5][6][7]. Brain metastases with concomitant liver and/or lung metastases occur more frequently than brain metastases alone [5].…”
mentioning
confidence: 99%
“…The most common primary sites are the sigmoid colon and rectum [5][6][7]. Brain metastases with concomitant liver and/or lung metastases occur more frequently than brain metastases alone [5]. Metastases to the brain most commonly occur by a hematogenous route via the portal venous system, through the liver, heart, lungs, and, finally, the carotids.…”
mentioning
confidence: 99%